2007
DOI: 10.1037/0278-6133.26.6.728
|View full text |Cite
|
Sign up to set email alerts
|

Computer-assisted intervention improves patient-centered diabetes care by increasing autonomy support.

Abstract: A patient-centered, computer-assisted intervention was effective in improving diabetes self-management outcomes, in part, because it increased patients' perception that their autonomy was supported which changed perceived competence. These findings support the self-determination model for health behavior change and the chronic care model and support the further study of the use of these technologies to motivate patients to improve their health outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
143
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 213 publications
(152 citation statements)
references
References 31 publications
5
143
0
1
Order By: Relevance
“…Early research was hampered by poorly defined terms, small scale studies or a reliance on qualitative research methods and is of limited empirical value (Slater, 2006). In a recent systematic review of the evidence (Brownie and Nancarrow, 2013), person-centred care is reported to have a positive impact on staff job satisfaction (Lehuluante et al, 2012), staff capacity to meet the needs of patients (Brownie and Nancarrow, 2013), cost effectiveness (Olsson et al, 2009), better levels of staff autonomy and empowerment (Williams et al, 2007). For patients, significant improvements are reported in physical outcomes and reduction in boredom (Brownie and Nancarrow, 2013).…”
Section: Study Backgroundmentioning
confidence: 99%
“…Early research was hampered by poorly defined terms, small scale studies or a reliance on qualitative research methods and is of limited empirical value (Slater, 2006). In a recent systematic review of the evidence (Brownie and Nancarrow, 2013), person-centred care is reported to have a positive impact on staff job satisfaction (Lehuluante et al, 2012), staff capacity to meet the needs of patients (Brownie and Nancarrow, 2013), cost effectiveness (Olsson et al, 2009), better levels of staff autonomy and empowerment (Williams et al, 2007). For patients, significant improvements are reported in physical outcomes and reduction in boredom (Brownie and Nancarrow, 2013).…”
Section: Study Backgroundmentioning
confidence: 99%
“…SDT-based research has shown that need support is key to integrative learning, such that when the act of learning is intrinsically motivated, it promotes a more thorough and deep understanding than learning guided by extrinsic factors (Niemiec & Ryan, 2009). In the health domain, computer-assisted health interventions have been shown to be more effective when they support basic needs (G. C. Williams, Lynch, & Glasgow, 2007), and research on exercise and weight loss (Vansteenkiste, Matos, Lens, & Soenens, 2007), the treatment of opioid dependence (Zeldman, Ryan, & Fiscella, 2004), and smoking cessation (G. C. Williams, GagnĂ©, Ryan, & Deci, 2002) highlights the importance of basic psychological needs to successful long-term regulation of health behaviors. Future intervention-focused video game research in the education and health domains should account for the need satisfaction provided by games when evaluating the influences of games.…”
Section: Future Directionsmentioning
confidence: 99%
“…Selfdetermination Theory (SDT; has been successfully employed in the domain of behaviour change (Williams, Lynch, & Glasgow, 2007). Self-determination Theory proposes that all individuals have three inherent psychological needs (i.e., the need to feel competent, autonomous, and related to others) and the degree to which these needs are perceived to be satisfied by the social environment effects important outcomes such as the quality of motivation, optimal functioning, sustained engagement and well-being.…”
Section: Introductionmentioning
confidence: 99%